Autonomous formation flight control of multiple UAVs with motion capture system - M. F., Abas (2013)
The evolution from a single entity to multiple entity flight has introduced numerous possibilities of performing multi task by using multiple agent system. In a multiple entity flight or formation, the search in a feasible way of acquiring individual position and attitude estimation system as a decentralized system has include the use of GPS, INS, Onboard Stereo Camera, Laser Range Finder and also Motion Capture System. The feasibility of each method of position and attitude estimation system as a decentralized system is presented as a part of this thesis. The use of onboard stereo camera is very promising for decentralized system but at the current state of onboard technology, the speed of the onboard stereo camera system is very slow. GPS in the other hand is widely used but the accuracy of such system for short range formation flight is questionable. For formation flight testing and evaluation, the used of motion capture system is very reliable. Formation flight for multiple agents Quad-rotor Aerial Vehicles (QAVs) has lead from conventional way of leader-follower formation flight to nature based formation flight. The first part of the formation in this thesis is based on a conventional way of leader-follower formation. The formation developed is a Simultaneous Angle and Distance Regulation (SADR). This type of formation is used for a curving or circular motion where by the distance of the leader-follower through the center and the angle between the leader and follower is regulated. Although the development has yielded good result, some negative attributes can be seen. The first is that the whole system relies directly on the leader. If the leader were nonfunctional, the whole system will be nonfunctional. There is no policy of algorithm were by the leader's task can be pass to other quad-rotor UAV.